Desenvolvimento regional, políticas públicas e efetividade da prestação jurisdicional: proposições com base no processo estrutural na resolução de conflitos pelo uso da água - Magalhães, Wellington (2024)
Economic and social development presupposes the planning and execution of public policies in several areas. The prevention of environmental damage and the compensation of ecosystem degradation have been a constant concern of humanity, occupying both the national and international agenda. In this context, this research work presents the problem involving the conflict over water use between medium and large irrigators producing grains in the region of the Rio Formoso Basin, in the State of Tocantins, whose causes are related to the failure of the State Executive Branch to implement the instruments that guide the management of water resources, as established by Federal Law No. 9,433/1997 and State Law No. 1,307/2002. The precariousness of monitoring water availability, combined with the lack of control over the granted flows, as well as operating rules in times of water scarcity, caused the Dueré, Formoso, Urubu and Xavante rivers to become large sandbanks, leading to Prosecutor's Office to petition the Judiciary of the State of Tocantins for the immediate suspension of all grants of right to use water resources in that region. The research problem focuses on the effectiveness of the jurisdictional provision when the judicialization of a public policy, in the specific case of this scientific investigation, of the water resources management policy and conflict over the use of water in the Formoso River Basin. The results made it possible to identify a new paradigm of judicial intervention in conflict resolution, especially those involving the implementation and management of public policies related to the exploitation of water resources.